First-principles investigation of wet-chemical routes for the hydrogenation of graphene. (November 2015) - Horbatenko, Yevhen; Choi, Min; Ruoff, Rodney S.; Bielawski, Christopher W.; Park, Noejung
Abstract: To investigate the microscopic mechanism for the wet-chemical hydrogenation of graphene, first principles density functional calculations were performed for the hydrogen transfer reaction between the graphene surface and a mixture of hydrogen carrier and electron donor. For the hydrogen transfer from CH3 OH to graphene, as commonly used in Birch-type reductions, the presence of alkali atoms is important not only because they donate electrons but also stabilize the CH3 O − . On the other hand, when a hydrogen carrier becomes charge neutral after the transfer, as for the case of CH3 NH3 +, the presence of alkali atoms is not essential, and the supply of electrons from an external source can lead to as favorable thermodynamics as that of alkali atoms. We suggest that, based on these results, a potentially more efficient experimental procedure can be designed.